Matrix-isolation and cryosolution-VCD spectra of α-pinene as benchmark for anharmonic vibrational spectra calculations. Issue 4 (12th January 2023) - Kreienborg, Nora M.; Yang, Qin; Pollok, Corina H.; Bloino, Julien; Merten, Christian
Abstract : Experimental VCD spectroscopy helps benchmarking computational approaches to identify resonances in anharmonic VPT2 spectra calculations. Abstract : The inclusion of anharmonicity in vibrational spectral analyis remains associated to small molecular systems with up to a dozen of atoms, with half a dozen of non-hydrogen atoms, typically thesize of propylene oxide. One may see two reasons for this: first of all, larger systems are often thought to be computationally too demanding (high computational costs) for a full anharmonic vibrational analysis. Second, the identification of resonances and their correction is often considered something only expert theoreticians could address because of the lack of unequivocal criteria. In this contribution, we illustrate that resonances can indeed become a complex problem, which can be handled almost transparently thanks to recent advances in vibrational perturbation theory (VPT2). The study also emphasizes the importance and the central role played by experiment in benchmarking novel theoretical approaches. In fact, we herein provide the currently highest resolution VCD spectra available for α- and β-pinene obtained under matrix-isolation conditions and in liquid Xenon as solvent. They are interpreted by VPT2 with novel tests for the identification of resonances. Hence, the study demonstrates the mutual stimulation of advances in both experimental techniques and computational models.